2009
DOI: 10.1590/s1984-82502009000300025
|View full text |Cite
|
Sign up to set email alerts
|

Development and in vitro evaluation of Letrozole loaded biodegradable nanoparticles for breast cancer therapy

Abstract: The objectives of our study were to prepare and evaluate a biodegradable nanoparticulate system of Letrozole (LTZ) intended for breast cancer therapy. LTZ loaded poly(lactide-co-glycolide) nanoparticles (LTZ-PLGA-NPs) were prepared by emulsion-solvent evaporation method using methylene chloride and polyvinyl alcohol. Percentage of drug (with respect to polymer) was selected as formulation variable. LTZ-PLGA-NPs were characterized by particle size, zeta potential, infrared spectra, drug entrapment efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…19,25 The PDI and zeta potential were found to increase with the increase in PLGA concentration ( Table 1). The results are in consensus with results published by Dey et al 26 The zeta potential of TIMP-1-NP PLGA3 formulation was -19.8±0.8 mV.…”
Section: Formulation Optimization and Characterizationsupporting
confidence: 92%
“…19,25 The PDI and zeta potential were found to increase with the increase in PLGA concentration ( Table 1). The results are in consensus with results published by Dey et al 26 The zeta potential of TIMP-1-NP PLGA3 formulation was -19.8±0.8 mV.…”
Section: Formulation Optimization and Characterizationsupporting
confidence: 92%
“…Moreover, an increase in particle size increases the length of diffusional pathways into the aqueous phase, thereby reducing the drug loss through diffusion and increasing the drug content (Budhian et al 2007). Dey et al have also found that encapsulation efficiency of nanoparticles increased from about 68 to 86% with the increment of their mean diameter from 64 nm to 255 nm (Dey et al 2009). Similar results were found by Gorner et al (Gorner et al 1999) where drug encapsulation efficiency grew with the increase in the particle size from about 19% for small particles to about 34% for medium and up to about 57% for large nanospheres which also complies with our earlier result (Feczko et al 2011) and strongly supports our present finding.…”
Section: Effect Of Sonication Duration On the Second Emulsificationmentioning
confidence: 89%
“…The lower encapsulation efficiencies obtained with the smaller particles was explained by the larger surface area of smaller droplets. Hence, during the emulsification step, a more direct contact between internal and external phases occurred which resulted in higher loss of model drug (HSA) by diffusion to the external medium (Dey et al 2009). Inversely, for larger droplets, the surface area per unit mass is comparatively smaller.…”
Section: Effect Of Sonication Duration On the Second Emulsificationmentioning
confidence: 99%
“…According to the literature, systems presenting spherical geometry, n=0.43 indicates Fickian diffusion, while n≥0.85 is related to case II transport (Peppas, 1985). Values between these limits suggest anomalous transport, i.e., the drug release initially depends on the polymer relaxation followed by Fickian diffusion (Dey et al, 2009).…”
Section: Resultsmentioning
confidence: 99%